1990
DOI: 10.1136/pgmj.66.780.827
|View full text |Cite
|
Sign up to set email alerts
|

Danazol in non-splenectomized patients with refractory idiopathic thrombocytopenic purpura

Abstract: Summary: Seven non-splenectomized patients with chronic refractory idiopathic thrombocytopenic purpura were treated with danazol 800 mg daily. All were glucocorticoid failures and four were refractory to all additional previous therapy. Five patients benefited from danazol and in two sustained normal platelet counts, for over 44 and 51 months, were observed. We conclude that danazol is useful for long term management of otherwise refractory idiopathic thrombocytopenic purpura. The advantage of danazol over spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…22,24 Unlike most previous studies, we administered low-tomedium dosages of danazol instead of the traditional dosage (600 mg/d). 13,[15][16][17][18][19][20][21] We also observed beneficial effects with this dosage regimen and found no significant correlation between danazol dose and response. Some previous studies had evaluated the efficiency of very low danazol doses (50 mg) for the treatment of ITP, and some of them reported good responses.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…22,24 Unlike most previous studies, we administered low-tomedium dosages of danazol instead of the traditional dosage (600 mg/d). 13,[15][16][17][18][19][20][21] We also observed beneficial effects with this dosage regimen and found no significant correlation between danazol dose and response. Some previous studies had evaluated the efficiency of very low danazol doses (50 mg) for the treatment of ITP, and some of them reported good responses.…”
Section: Discussionmentioning
confidence: 87%
“…Farkas et al 29 suggested that when administered at the lowest effective dose, danazol does not induce liver injury. 17 3 800 3/3 NA 1/3 0/3 Nalli et al 18 14 600 5/50 2-12 NA NA Edelmann et al 19 7 800 5/7 NA NA 1/7 McVerry et al 20 10 400-600 3/10 1-6 2/3 2/10 Fenaux et al 21 22 600 7/22 NA 5/7 NA Mylvaganam et al 22 15 50 10/15 NA NA NA Nozaki et al 23 17 50 1/13 NA 0/1 4/17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La risposta fu eccellente in 11 (>100 x 10 9 /l piastrine, per almeno 2 mesi), buona in 2 (50-100 x 10 9 /l piastrine per almeno 2 mesi), discreta in altri 2, pari ad un miglioramento complessivo nel 68% dei pazienti. Le diverse casistiche hanno riportato percentuali variabili di risposta al danazolo, che vanno dal 10% all'80% (Agnello et al, 1983;Ahn et al, 1983;Buelli et al, 1985;Mc Verry et al, 1985;Almagro 1985;Ambriz et al, 1986;Mazzucconi et al 1987;Manobaran 1987;Nalli G, et al, 1988;Schreiber et al 1987;Kotlarek-Haus et al, 1987;Ahn et al, 1989;Edelmann et al, 1990;Flores et al, 1990;Arrowsmith et al, 1986;Maloisel et al, 2004;Andrès et al, 2003). Nel complesso però la percentuale di risposta può essere stimata intorno al 50%, indipendentemente dal precedente trattamento della ITP.…”
Section: Danazolounclassified
“…[63][64][65][66][67][68][69] One factor that may account for this variation is heterogeneity in dosing, with some studies investigating low-dose danazol (50 mg orally once per day) 64,65 compared with conventional dosing (400 to 800 mg divided into 2 to 4 doses per day). 63,66,67,69 The effect of danazol appears to be greatest when patients are able to remain on therapy for a prolonged period. In a series of 96 patients, 7 (70%) of the 10 patients in whom danazol therapy was discontinued relapsed within 6 months.…”
Section: Tiermentioning
confidence: 99%